2010
DOI: 10.1371/journal.pone.0014020
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in mGluR5 Expression and Signaling in Lewy Body Disease and in Transgenic Models of Alpha-Synucleinopathy – Implications for Excitotoxicity

Abstract: Dementia with Lewy bodies (DLB) and Parkinson's Disease (PD) are neurodegenerative disorders of the aging population characterized by the abnormal accumulation of alpha-synuclein (alpha-syn). Previous studies have suggested that excitotoxicity may contribute to neurodegeneration in these disorders, however the underlying mechanisms and their relationship to alpha-syn remain unclear. For this study we proposed that accumulation of alpha-syn might result in alterations in metabotropic glutamate receptors (mGluR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 88 publications
6
58
0
Order By: Relevance
“…Other studies have shown that β-arrestins and GRK6 are overexpressed in mouse and monkey models of PD (43,44), and that lentiviral-mediated overexpression of GRK6 in rodent and monkey models of PD reduces LIDs (30). GRK6, which lies upstream of β-arrestins in the GPCR signaling cascade, presumably promotes β-arrestin-dependent signaling (45)(46)(47).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have shown that β-arrestins and GRK6 are overexpressed in mouse and monkey models of PD (43,44), and that lentiviral-mediated overexpression of GRK6 in rodent and monkey models of PD reduces LIDs (30). GRK6, which lies upstream of β-arrestins in the GPCR signaling cascade, presumably promotes β-arrestin-dependent signaling (45)(46)(47).…”
Section: Resultsmentioning
confidence: 99%
“…While in the previous study we analyzed PDGF-α-syn (line D) mice [19], for this new study we investigated the mThy1-α-syn (line 61), as well as crosses with the mThy1-APP mutant tg mouse model of DLB. This bigenic mThy1-α-syn/APP mutant tg line is new and has not been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research using [ 35 S]GTPcS (guanosine 5 0 -O-[c-thio]triphosphate) functional binding autoradiography has demonstrated a similar process in PD, whereby compensatory mechanisms maintain dopaminergic neurotransmission, despite a reduction in D2 receptor density, via increases in D2 receptor-G protein signal transduction in the caudate (Farkas et al 2012). Moreover, previous postmortem brain research has shown an increase in mGluR5 immunoreactivity in the putamen in patients with PD, implying that upregulation of these receptors also occurs in PD (Price et al 2010). Despite the clear loss of neurons within the putamen and caudate in our study, the total cell count was essentially unchanged in HD samples compared with control samples, suggesting reactive gliosis.…”
Section: Discussionmentioning
confidence: 94%
“…Data from murine models of HD found no change in the density of this receptor in the brains of symptomatic animals (Cha et al 1998), whereas brains of patients with PD show increased mGluR5 levels (Price et al 2010). Given the similarity in the clinical features of HD and PD with levodopa-induced dyskinesia (PD-LID), we hypothesized that the pattern of mGluR5 density, as well as Enk-and SP-containing neurons, would be similar in the basal ganglia of patients with these two conditions.…”
Section: Introductionmentioning
confidence: 98%